Processing aid for tensile CPVC (Chlorinated Polyvinyl Chloride) plate and preparation process of processing aid
By functionalizing the surface of glass fiber to form an epoxy cross-linked layer and an elastic layer, the problem of decreased tensile strength and impact performance of CPVC sheets under high temperature and high humidity environments is solved, and the long-term stability of the sheets in high temperature and high humidity environments is achieved.
Patent Information
- Application Number
- CN202610030444.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-12
- Publication Date
- 2026-02-06
- Estimated Expiration
- 2046-01-12
AI Technical Summary
When existing CPVC sheets are used in high temperature and high humidity environments, the interface between glass fiber and CPVC matrix is weak, resulting in stress concentration, a significant decrease in tensile strength and impact performance, and easy aging of polybutadiene rubber, which reduces toughness.
A surface functionalization treatment of glass fiber was carried out using KH-550 hydrolysate, bisphenol A type epoxy resin solution, ODI and GMA to form Si-O-Si bonds and an epoxy crosslinking layer. An elastic layer and a BA-MMA copolymer outer layer were grafted onto the outside of the glass fiber to prepare a processing aid for tensile-resistant CPVC sheets.
In high-temperature and high-humidity environments, processing aids can maintain high tensile strength and impact strength. Through the stability of Si-O-Si bonds and the hydrophobic barrier of urethane flexible segments, hydrolysis is inhibited, thus maintaining the long-term stability of the board structure.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of composite processing aids, and particularly relates to a processing aid for anti-tensile CPVC plate and a preparation process thereof. BACKGROUND
[0002] CPVC plate is a kind of high-performance thermoplastic plate. In the prior art, glass fibers are often added to improve the tensile strength of the CPVC plate. However, due to the high rigidity of the glass fibers and the weak interface bonding between the glass fibers and the CPVC matrix, stress concentration is easily caused when the glass fibers are under stress, which increases the brittleness of the plate and significantly reduces the impact strength and elongation at break, thereby weakening the impact resistance of the plate.
[0003] A Chinese patent document with the publication number CN111423673B discloses a heat-resistant and high-temperature-resistant PVC power pipe and a preparation method thereof, and discloses a modified filler. Deionized water, alpha-methylstyrene, acrylonitrile, tertiary dodecanethiol, cumene hydroperoxide, and soap of rosin acid are uniformly mixed to obtain a monomer mixture. In a reaction kettle, deionized water, glucose, sodium pyrophosphate, potassium fatty acid salt, ferrous sulfate solution, potassium rosin acid, potassium hydroxide, and polybutadiene latex are added. Modified montmorillonite is added under a nitrogen atmosphere. After stirring and dispersing, nano glass fibers are added and heated. The monomer mixture is added to the reaction kettle for reaction through a peristaltic pump. After demulsification, filtration, dehydration, and drying, a composite modified filler is obtained.
[0004] The composite modified filler can be used as a processing aid to prepare a plate by blending with CPVC. When the plate is used, the glass fibers can effectively improve the tensile strength of the plate, and the polybutadiene rubber has excellent toughening performance and can absorb impact energy to improve the toughness of the plate. However, when the above-mentioned plate is used for a long time in a high-temperature and high-humidity environment, the polybutadiene rubber is prone to aging, which causes the plate to harden and become brittle. At the same time, the silicon-oxygen bond on the surface of the glass fibers may be hydrolyzed under the condition of heat and humidity, which causes the glass fibers to debond with the CPVC matrix, causing local stress concentration, and significantly reducing the tensile strength and impact performance of the plate. SUMMARY
[0005] The application provides a processing aid for anti-tensile CPVC plate and a preparation process thereof. The prepared processing aid can be blended with CPVC to prepare a CPVC plate. When the plate is used in a high-temperature and high-humidity environment, it can maintain high tensile strength and impact strength for a long time.
[0006] To solve the above problems, the application adopts the following technical solutions: A preparation process of a processing aid for anti-tensile CPVC plate, comprising the following steps: S1. Disperse glass fibers in KH-550 hydrolysate, stir and react. After washing and drying, disperse them in bisphenol A epoxy resin solution, heat and stir and react. After washing and drying, disperse them in ODI solution, heat and stir and react. After washing, disperse them in GMA solution, heat and stir and react. After washing and drying, obtain modified glass fibers. S2. Add dispersant to deionized water and mix well to obtain a dispersion. Disperse the modified glass fiber in the dispersion, add initiator and BA, heat and stir to react. Add initiator and MMA, stir to react, and obtain the processing aid after washing and drying.
[0007] This invention uses KH-550 hydrolysate, bisphenol A epoxy resin solution, ODI, and GMA to perform surface functionalization treatment on glass fibers in sequence to obtain modified glass fibers. An elastic layer and a BA-MMA copolymer outer layer are then grafted onto the modified glass fibers in sequence using BA and MMA to obtain a processing aid. When CPVC sheets prepared by blending this processing aid with CPVC are used in high temperature and high humidity environments for a long time, they can effectively maintain high tensile strength and good impact resistance.
[0008] In the preparation of modified glass fiber, a condensation reaction occurs between the silanol groups of oligomeric silanol in KH-550 hydrolysate and the silanol groups on the glass fiber surface to generate Si-O-Si bonds, introducing primary amino groups into the glass fiber surface. The epoxy groups in the bisphenol A epoxy resin solution undergo a ring-opening reaction with the primary amino groups, introducing an epoxy crosslinking layer and hydroxyl groups into the glass fiber surface. Some of the hydroxyl groups react with the isocyanate groups of ODI, grafting long-chain octadecyl urethane flexible segments onto the glass fiber surface. Another part of the hydroxyl groups undergoes a ring-opening reaction with the epoxy groups of GMA, introducing carbon-carbon double bonds into the glass fiber surface, thus obtaining modified glass fiber. Under the initiation of an initiator, a free radical copolymerization reaction occurs between the carbon-carbon double bonds on the modified glass fiber surface and the carbon-carbon double bonds of BA, forming an elastic layer mainly composed of PBA on the modified glass fiber surface. Under the initiation of an initiator, MMA and the elastic layer undergo a free radical copolymerization reaction to form a BA-MMA copolymer outer layer, thus obtaining a processing aid.
[0009] The glass fibers and epoxy cross-linked layer on their surface in the processing aid have high tensile modulus, which can improve the tensile strength of CPVC sheets. The polarity of the BA-MMA copolymer outer layer matches that of CPVC, and the two have good compatibility, which is conducive to the uniform dispersion of the processing aid in the CPVC sheet. The processing aid contains a soft elastic layer and urethane flexible segments, which alleviates the stress concentration caused by the rigid glass fibers and the epoxy cross-linked layer on their surface, and improves the impact strength of CPVC sheets. The urethane flexible segments and elastic layer form a hydrophobic barrier, which effectively prevents external water molecules from diffusing into the processing aid and inhibits the Si-O-Si bonds in the modified glass fibers from contacting water molecules and undergoing hydrolysis. This maintains the structural stability of the epoxy cross-linked layer, urethane flexible segments, elastic layer and BA-MMA copolymer outer layer in high temperature and high humidity environments for a long time. As a result, CPVC sheets can maintain high tensile strength and impact strength for a long time when used in high temperature and high humidity environments.
[0010] Furthermore, the KH-550 hydrolysate is prepared by mixing anhydrous ethanol, KH-550, and deionized water, adding acetic acid solution to adjust the pH to 4-5, and stirring at 300-400 rpm for 1.5-2.5 h to obtain the KH-550 hydrolysate.
[0011] Under acid catalysis, KH-550 undergoes a hydrolysis reaction with water molecules to generate monomeric silanols. These monomeric silanols then undergo a condensation reaction to generate oligomeric silanols. These oligomeric silanols contain primary amino groups and silanols, which provide the molecular basis for subsequent condensation reactions with silanols on the glass fiber surface to generate Si-O-Si bonds, thereby introducing primary amino groups onto the glass fiber surface.
[0012] Furthermore, the bisphenol A type epoxy resin solution is obtained by mixing bisphenol A diglycidyl ether, bisphenol A type epoxy resin with a degree of polymerization of 2, and acetone.
[0013] The epoxy groups of bisphenol A diglycidyl ether and bisphenol A type epoxy resin can undergo ring-opening addition reactions with primary amino groups on the surface of glass fibers. Among them, the bisphenol A type epoxy resin with a degree of polymerization of 2 contains multiple rigid repeating units of bisphenol A, which is conducive to forming a dense epoxy crosslinking network on the surface of glass fibers and simultaneously introducing hydroxyl groups.
[0014] Furthermore, the ODI solution is obtained by mixing ODI, ethyl acetate, and DBTDL in an inert atmosphere.
[0015] Furthermore, the GMA solution is obtained by mixing GMA, HQ, and THF.
[0016] HQ, as a polymerization inhibitor, can suppress premature self-polymerization between GMA molecules, allowing GMA molecules to react with the hydroxyl groups on the glass fiber surface in monomer form, thereby covalently grafting carbon-carbon double bonds onto the glass fiber surface, providing a molecular basis for the subsequent construction of an elastic layer based on PBA on the glass fiber surface.
[0017] Further, in step S1, glass fiber is added to KH-550 hydrolysate, stirred at 700-800 rpm for 15-25 min, then stirred at 300-400 rpm for 1-2 h. After washing with anhydrous ethanol and drying, it is added to bisphenol A epoxy resin solution, stirred at 700-800 rpm for 15-25 min, heated to 65-70℃, stirred at 300-400 rpm for 2-3 h, washed with acetone, and dried in an environment of 50-60℃ and 8-10 kPa for 2-3 h, and then kept in an inert atmosphere. The modified glass fiber is added to the ODI solution under protection and stirred at 700-800 rpm for 15-25 min. The temperature is raised to 55-65℃ and stirred at 300-400 rpm for 1-2 h. After washing with ethyl acetate and THF, it is added to the GMA solution and stirred at 700-800 rpm for 15-25 min. The temperature is raised to 60-70℃ and stirred at 300-400 rpm for 1.5-2.5 h. After washing with THF and ethyl acetate, it is dried in an environment of 50-60℃ and 8-10 kPa for 2-3 h to obtain the modified glass fiber.
[0018] Furthermore, the drying temperature is 100-110℃, and the drying time is 2-3 hours.
[0019] After treatment with KH-550 hydrolysate, primary amino groups are grafted onto the surface of glass fibers via Si-O-Si bonds. The fibers are then dried to remove surface moisture, preventing water molecules from consuming the epoxy groups in the bisphenol A type epoxy resin solution. This allows bisphenol A diglycidyl ether and the bisphenol A type epoxy resin to fully react with the primary amino groups, facilitating the formation of an epoxy cross-linked layer on the glass fiber surface and the simultaneous generation of hydroxyl groups. Subsequent vacuum drying removes adsorbed moisture from the glass fiber surface, preventing side reactions between water molecules and isocyanate groups in the ODI solution. Under the catalysis of DBTDL, the isocyanate groups of ODI react with some of the hydroxyl groups on the glass fiber surface, covalently grafting urethane flexible segments onto the epoxy cross-linked layer. Meanwhile, the epoxy groups in the GMA solution react with another portion of the hydroxyl groups on the glass fiber surface, covalently grafting carbon-carbon double bonds onto the epoxy cross-linked layer, resulting in modified glass fibers.
[0020] Further, in step S2, modified glass fiber is added to the dispersion, stirred at 700-800 rpm for 20-30 min, initiator and BA are added and mixed, the temperature is raised to 70-80℃, stirred at 300-400 rpm for 1.5-2.5 h, initiator and MMA are added, stirred at 350-400 rpm for 2-3 h, filtered, washed with deionized water and anhydrous ethanol, and dried in an environment of 60-70℃ and 6-8 kPa for 4-6 h to obtain the processing aid.
[0021] The initiator was added to the dispersion in two stages to maintain a low free radical concentration. The first addition of the initiator, due to its low free radical concentration, effectively inhibited the homopolymerization of BA in the dispersion, promoting the preferential formation of active centers at the carbon-carbon double bond sites on the modified glass fiber surface. This, in turn, initiated the graft polymerization of BA monomers, constructing a PBA-dominated elastic layer on the modified glass fiber surface. The initiator was then added during the addition of MMA to maintain a low free radical concentration, promoting the reaction between MMA monomers and the active chain ends of PBA, thereby forming a BA-MMA copolymer outer layer.
[0022] A processing aid for tensile CPVC sheets, prepared by the above-mentioned process for preparing processing aids for tensile CPVC sheets, comprises the following raw materials in parts by weight: 15-20 parts modified glass fiber, 18-25 parts BA, 0.6-1.0 parts initiator, and 3-5 parts MMA; wherein the modified glass fiber comprises the following raw materials in parts by weight: 17-25 parts glass fiber, 210-215 parts KH-550 hydrolysate, 142-155 parts bisphenol A epoxy resin solution, 115-129 parts ODI solution, and 143-156 parts GMA solution; wherein the modified glass fiber has a length of 1-3 mm and a diameter of 7-13 μm; and wherein the initiator is KPS.
[0023] Further, the KH-550 hydrolysate comprises the following raw materials in parts by weight: 275-286 parts anhydrous ethanol, 28-35 parts KH-550, and 16-20 parts deionized water; the bisphenol A epoxy resin solution comprises 25-35 parts bisphenol A diglycidyl ether, 5-9 parts bisphenol A epoxy resin with a degree of polymerization of 2, and 280-290 parts acetone; the ODI solution comprises 4-8 parts ODI, 95-106 parts ethyl acetate, and 0.2-0.3 parts DBTDL; the GMA solution comprises 10-16 parts GMA, 0.02-0.04 parts HQ, and 205-217 parts THF; the dispersion comprises 3-5 parts dispersant and 240-255 parts deionized water; the dispersant is SDS.
[0024] The beneficial effects of this invention are: This invention sequentially treats glass fibers with KH-550 hydrolysate, bisphenol A type epoxy resin solution, ODI, and GMA. Primary amino groups are introduced onto the outside of the glass fibers through Si-O-Si bonds to construct an epoxy crosslinking layer. The epoxy crosslinking layer is covalently grafted with urethane flexible segments and carbon-carbon double bonds to obtain modified glass fibers. Under the action of an initiator, an elastic layer and a BA-MMA copolymer outer layer are constructed on the outside of the modified glass fibers through BA and MMA to obtain a processing aid. This processing aid can be mixed with CPVC to prepare CPVC sheets. The BA-MMA copolymer outer layer in the processing aids prepared in this invention helps to achieve uniform dispersion of the processing aids. The glass fiber and epoxy crosslinking layer can improve the tensile strength of the board, and the elastic layer and urethane flexible segments can improve the impact strength of the board. The urethane flexible segments and the elastic layer together form a hydrophobic barrier, which effectively inhibits the contact and hydrolysis of Si-O-Si bonds with water molecules. This allows the structure of the epoxy crosslinking layer, urethane flexible segments, elastic layer and BA-MMA copolymer outer layer to maintain long-term stability in high temperature and high humidity environments. When CPVC boards are used in high temperature and high humidity environments, they can maintain high tensile strength and impact strength for a long time. Detailed Implementation
[0025] Example 1 Mix 280g anhydrous ethanol, 30g KH-550 (γ-aminopropyltriethoxysilane), and 17g deionized water, and adjust the pH to 4 by adding 4wt% acetic acid solution. Stir at 350rpm for 2h to obtain KH-550 hydrolysate. Add 25g bisphenol A diglycidyl ether and 5g bisphenol A type epoxy resin with a degree of polymerization of 2 to 285g acetone and stir at 300rpm for 15min to obtain bisphenol A type epoxy resin solution. Under a nitrogen atmosphere, add 5g ODI (octadecyl isocyanate) and 0.2g DBTDL (dibutyltin dilaurate) to 100g ethyl acetate and stir at 300rpm for 15min to obtain ODI solution. Add 10g GMA (glycidyl methacrylate) and 0.02g HQ (hydroquinone) to 205g THF (tetrahydrofuran) and stir at 300rpm for 15min to obtain GMA solution.
[0026] 20g of glass fiber with a length of 3mm and a diameter of 10μm was added to 210g of KH-550 hydrolysate. The mixture was stirred at 800rpm for 20min, then at 350rpm for 2h. After filtration, the fiber was washed twice with anhydrous ethanol and dried at 100℃ for 2h. After cooling to room temperature, the fiber was added to 150g of bisphenol A epoxy resin solution. The mixture was stirred at 800rpm for 20min, heated to 70℃, and stirred at 350rpm for 3h. After filtration, the fiber was washed twice with acetone and dried at 60℃ and 8kPa for 2h. The fiber was then added to 120g of ODI solution under a nitrogen atmosphere. The mixture was stirred at 750rpm for 25min, heated to 65℃, and stirred at 300rpm for 1.5h. After filtration, the fiber was washed once with ethyl acetate and once with THF. The mixture was then added to 150g of... In GMA solution, stir at 700 rpm for 15 min, heat to 70℃, stir at 300 rpm for 2 h, filter, wash once with THF and once with ethyl acetate, and dry in an environment of 60℃ and 8 kPa for 2 h to obtain modified glass fiber.
[0027] Add 3g SDS (sodium dodecyl sulfate) to 250g deionized water and stir at 300rpm for 10min to obtain a dispersion. Add 16g modified glass fiber to the dispersion and stir at 800rpm for 20min. Add 0.3g KPS (potassium persulfate) and 20g BA (butyl acrylate) and stir at 300rpm for 25min. Heat to 75℃ and stir at 350rpm for 1.5h. Add 0.3g KPS and slowly add 3g MMA (methyl methacrylate) while stirring at 400rpm. After the addition is complete, stir at 350rpm for 2h. Filter, wash twice with deionized water and once with anhydrous ethanol, and dry at 60℃ and 8kPa for 4h to obtain the processing aid.
[0028] Example 2 Mix 275g anhydrous ethanol, 35g KH-550, and 20g deionized water, and adjust the pH to 4 by adding 4wt% acetic acid solution. Stir at 350rpm for 2.5h to obtain KH-550 hydrolysate. Add 30g bisphenol A diglycidyl ether and 6g bisphenol A type epoxy resin with a degree of polymerization of 2 to 290g acetone and stir at 300rpm for 15min to obtain bisphenol A type epoxy resin solution. Under a nitrogen atmosphere, add 4g ODI and 0.2g DBTDL to 103g ethyl acetate and stir at 300rpm for 15min to obtain ODI solution. Add 12g GMA and 0.03g HQ to 210g THF and stir at 300rpm for 15min to obtain GMA solution.
[0029] 19g of glass fiber with a length of 1mm and a diameter of 11μm was added to 212g of KH-550 hydrolysate. The mixture was stirred at 750rpm for 20min, then at 300rpm for 2h. After filtration, the fiber was washed twice with anhydrous ethanol and dried at 105℃ for 2.5h. After cooling to room temperature, 142g of bisphenol A epoxy resin solution was added. The mixture was stirred at 800rpm for 15min, heated to 65℃, and stirred at 300rpm for 2h. After filtration, the fiber was washed twice with acetone and dried at 52℃ and 8kPa for 2h. 118g of ODI solution under a nitrogen atmosphere was added. The mixture was stirred at 750rpm for 20min, heated to 55℃, and stirred at 300rpm for 2h. After filtration, the fiber was washed once with ethyl acetate and once with THF. 156g of… In GMA solution, stir at 700 rpm for 25 min, heat to 60℃, stir at 300 rpm for 2.5 h, filter, wash once with THF, wash once with ethyl acetate, and dry in an environment of 52℃ and 8 kPa for 2 h to obtain modified glass fiber.
[0030] Add 4g SDS to 255g deionized water and stir at 300rpm for 10min to obtain a dispersion. Add 20g modified glass fiber to the dispersion and stir at 700rpm for 25min. Add 0.4g KPS and 18g BA and stir at 300rpm for 25min. Heat to 80℃ and stir at 300rpm for 2.5h. Add 0.5g KPS and slowly add 4g MMA while stirring at 400rpm. After the addition is complete, stir at 350rpm for 2h. Filter, wash twice with deionized water and once with anhydrous ethanol, and dry at 65℃ and 6kPa for 4h to obtain the processing aid.
[0031] Example 3 Mix 275g anhydrous ethanol, 29g KH-550, and 18g deionized water, and adjust the pH to 4.5 by adding 4wt% acetic acid solution dropwise. Stir at 350rpm for 2h to obtain KH-550 hydrolysate. Add 30g bisphenol A diglycidyl ether and 8g bisphenol A type epoxy resin with a degree of polymerization of 2 to 285g acetone and stir at 300rpm for 15min to obtain bisphenol A type epoxy resin solution. Under a nitrogen atmosphere, add 6g ODI and 0.25g DBTDL to 95g ethyl acetate and stir at 300rpm for 15min to obtain ODI solution. Add 16g GMA and 0.04g HQ to 215g THF and stir at 300rpm for 15min to obtain GMA solution.
[0032] 17g of glass fiber with a length of 2mm and a diameter of 13μm was added to 215g of KH-550 hydrolysate. The mixture was stirred at 750rpm for 20min, then at 300rpm for 2h. After filtration, the fiber was washed twice with anhydrous ethanol and dried at 105℃ for 2.5h. After cooling to room temperature, 146g of bisphenol A epoxy resin solution was added. The mixture was stirred at 800rpm for 15min, heated to 65℃, and stirred at 300rpm for 2h. After filtration, the fiber was washed twice with acetone and dried at 55℃ and 9kPa for 3h. 129g of ODI solution under a nitrogen atmosphere was added. The mixture was stirred at 750rpm for 20min, heated to 55℃, and stirred at 300rpm for 2h. After filtration, the fiber was washed once with ethyl acetate and once with THF. 147g of… In GMA solution, stir at 700 rpm for 25 min, heat to 60℃, stir at 300 rpm for 2.5 h, filter, wash once with THF, wash once with ethyl acetate, and dry in an environment of 55℃ and 9 kPa for 3 h to obtain modified glass fiber.
[0033] Add 5g SDS to 240g deionized water and stir at 300rpm for 10min to obtain a dispersion. Add 15g modified glass fiber to the dispersion and stir at 700rpm for 25min. Add 0.3g KPS and 23g BA and stir at 300rpm for 25min. Heat to 76℃ and stir at 300rpm for 2.5h. Add 0.4g KPS and slowly add 5g MMA while stirring at 400rpm. After the addition is complete, stir at 350rpm for 2h. Filter, wash twice with deionized water and once with anhydrous ethanol, and dry in an environment of 65℃ and 7kPa for 5h to obtain the processing aid.
[0034] Example 4 Mix 282g anhydrous ethanol, 28g KH-550, and 16g deionized water, and adjust the pH to 4.5 by adding 4wt% acetic acid solution dropwise. Stir at 400rpm for 1.5h to obtain KH-550 hydrolysate. Add 35g bisphenol A diglycidyl ether and 9g bisphenol A type epoxy resin with a degree of polymerization of 2 to 280g acetone and stir at 300rpm for 15min to obtain bisphenol A type epoxy resin solution. Under a nitrogen atmosphere, add 8g ODI and 0.25g DBTDL to 106g ethyl acetate and stir at 300rpm for 15min to obtain ODI solution. Add 14g GMA and 0.02g HQ to 217g THF and stir at 300rpm for 15min to obtain GMA solution.
[0035] Add 20g of glass fiber with a length of 2mm and a diameter of 7μm to 212g In KH-550 hydrolysate, stir at 800 rpm for 15 min, then at 400 rpm for 1 h. Filter, wash twice with anhydrous ethanol, dry at 110℃ for 2 h, cool to room temperature, add 155 g of bisphenol A epoxy resin solution, stir at 700 rpm for 25 min, heat to 70℃, stir at 400 rpm for 3 h, filter, wash twice with acetone, dry at 60℃ and 10 kPa for 2.5 h, add 125 g of ODI solution under nitrogen atmosphere, stir at 800 rpm for 15 min, heat to 60℃, stir at 350 rpm for 1.5 h, filter, wash once with ethyl acetate and once with THF, add 143 g of GMA solution, stir at 800 rpm for 15 min, heat to 63℃, stir at 350 rpm for 2 h, filter, wash once with THF and once with ethyl acetate, dry at 60℃ and 10 kPa for 2.5 h to obtain modified glass fiber.
[0036] Add 3g SDS to 242g deionized water and stir at 300rpm for 10min to obtain a dispersion. Add 17g modified glass fiber to the dispersion and stir at 800rpm for 20min. Add 0.5g KPS and 24g BA and stir at 300rpm for 25min. Heat to 70℃ and stir at 350rpm for 2h. Add 0.4g KPS and slowly add 5g MMA while stirring at 400rpm. After the addition is complete, stir at 400rpm for 3h. Filter, wash twice with deionized water and once with anhydrous ethanol, and dry at 70℃ and 8kPa for 6h to obtain the processing aid.
[0037] Example 5 Mix 286g anhydrous ethanol, 32g KH-550, and 20g deionized water, and adjust the pH to 5 by adding 4wt% acetic acid solution. Stir at 300rpm for 2h to obtain KH-550 hydrolysate. Add 33g bisphenol A diglycidyl ether and 7g bisphenol A type epoxy resin with a degree of polymerization of 2 to 288g acetone and stir at 300rpm for 15min to obtain bisphenol A type epoxy resin solution. Under a nitrogen atmosphere, add 5g ODI and 0.3g DBTDL to 105g ethyl acetate and stir at 300rpm for 15min to obtain ODI solution. Add 15g GMA and 0.03g HQ to 208g THF and stir at 300rpm for 15min to obtain GMA solution.
[0038] 25g of glass fiber with a length of 1mm and a diameter of 9μm was added to 213g of KH-550 hydrolysate. The mixture was stirred at 800rpm for 15min, then at 400rpm for 1h. After filtration, the fiber was washed twice with anhydrous ethanol and dried at 110℃ for 2h. After cooling to room temperature, 152g of bisphenol A epoxy resin solution was added. The mixture was stirred at 700rpm for 25min, heated to 70℃, and stirred at 400rpm for 3h. After filtration, the fiber was washed twice with acetone and dried at 53℃ and 8kPa for 2h. 115g of ODI solution under a nitrogen atmosphere was added. The mixture was stirred at 800rpm for 15min, heated to 60℃, and stirred at 350rpm for 1.5h. After filtration, the fiber was washed once with ethyl acetate and once with THF. 152g of… In GMA solution, stir at 800 rpm for 15 min, heat to 63℃, stir at 350 rpm for 2 h, filter, wash once with THF and once with ethyl acetate, and dry in an environment of 53℃ and 8 kPa for 2 h to obtain modified glass fiber.
[0039] Add 4g SDS to 253g deionized water and stir at 300rpm for 10min to obtain a dispersion. Add 19g modified glass fiber to the dispersion and stir at 800rpm for 20min. Add 0.5g KPS and 25g BA and stir at 300rpm for 25min. Heat to 75℃ and stir at 350rpm for 2h. Add 0.5g KPS and slowly add 4g MMA while stirring at 400rpm. After the addition is complete, stir at 400rpm for 3h. Filter, wash twice with deionized water and once with anhydrous ethanol, and dry at 70℃ and 6kPa for 5h to obtain the processing aid.
[0040] Example 6 Mix 278g anhydrous ethanol, 33g KH-550, and 19g deionized water, and adjust the pH to 5 by adding 4wt% acetic acid solution dropwise. Stir at 350rpm for 2.5h to obtain KH-550 hydrolysate. Add 28g bisphenol A diglycidyl ether and 5g bisphenol A type epoxy resin with a degree of polymerization of 2 to 282g acetone and stir at 300rpm for 15min to obtain bisphenol A type epoxy resin solution. Under a nitrogen atmosphere, add 6g ODI and 0.3g DBTDL to 102g ethyl acetate and stir at 300rpm for 15min to obtain ODI solution. Add 13g GMA and 0.04g HQ to 212g THF and stir at 300rpm for 15min to obtain GMA solution.
[0041] 23g of glass fiber with a length of 3mm and a diameter of 10μm was added to 215g of KH-550 hydrolysate. The mixture was stirred at 700rpm for 25min, then at 350rpm for 1.5h. After filtration, the fiber was washed twice with anhydrous ethanol and dried at 105℃ for 3h. After cooling to room temperature, 155g of bisphenol A epoxy resin solution was added. The mixture was stirred at 750rpm for 20min, heated to 67℃, and stirred at 350rpm for 2.5h. After filtration, the fiber was washed twice with acetone and dried at 56℃ and 10kPa for 2.5h. 115g of ODI solution under a nitrogen atmosphere was added. The mixture was stirred at 700rpm for 25min, heated to 65℃, and stirred at 400rpm for 1h. After filtration, the fiber was washed once with ethyl acetate and once with THF. 143g of… In GMA solution, stir at 750 rpm for 20 min, heat to 70℃, stir at 400 rpm for 1.5 h, filter, wash once with THF and once with ethyl acetate, and dry in an environment of 56℃ and 10 kPa for 2.5 h to obtain modified glass fiber.
[0042] Add 5g SDS to 248g deionized water and stir at 300rpm for 10min to obtain a dispersion. Add 20g modified glass fiber to the dispersion and stir at 750rpm for 30min. Add 0.5g KPS and 22g BA and stir at 300rpm for 25min. Heat to 80℃ and stir at 400rpm for 1.5h. Add 0.3g KPS and slowly add 3g MMA while stirring at 400rpm. After the addition is complete, stir at 380rpm for 2.5h. Filter, wash twice with deionized water and once with anhydrous ethanol, and dry in an environment of 67℃ and 7kPa for 4h to obtain the processing aid.
[0043] The present invention also includes comparative examples and related experiments.
[0044] Comparative Example 1 The difference between this comparative example and Example 6 is that the glass fiber was not treated with bisphenol A type epoxy resin solution. The remaining operation steps and conditions are the same as in Example 6, and the processing aid is obtained.
[0045] Comparative Example 2 The difference between this comparative example and Example 6 is that ODI solution was not used to treat the glass fiber. The remaining operation steps and conditions are the same as in Example 6, and the processing aid is obtained.
[0046] Comparative Example 3 The difference between this comparative example and Example 6 is that BA was not added during the preparation of the processing aid. The remaining operation steps and conditions were the same as in Example 6, and the processing aid was obtained.
[0047] Comparative Example 4 The difference between this comparative example and Example 6 is that MMA was not added during the preparation of the processing aid. The remaining operation steps and conditions are the same as in Example 6, and the processing aid is obtained.
[0048] Performance testing Take 75g of the processing aid prepared in each example and comparative example, and divide it into fifteen groups. Add 100g of CPVC resin to each group of samples and stir at 1000rpm for 10min. Then add the mixture to the mold cavity of a flat vulcanizing machine. Set the upper and lower plate temperatures to 180℃ and the pressure to 15MPa. Hot press for 10min, cool down to 35℃ and demold to obtain CPVC sheets. Each example and comparative example corresponds to fifteen sheet samples. Each sheet metal sample was placed in a constant temperature and humidity test chamber, with the temperature set at 85℃ and the relative humidity at 85%. On days 0, 10, 50, 100, and 200, three samples were taken from each example and comparative example as specimens and placed in a constant temperature and humidity test chamber at 23℃ and 50% relative humidity for 48 hours. The tensile strength (MPa) of each specimen was tested according to GB / T 1040.2-2022 standard, and the impact strength (kJ / m²) of each specimen was tested according to GB / T 1843–2008 standard. 2 To conduct the test, follow the formula below:
[0049]
[0050] The tensile strength attenuation rate (%) and impact strength attenuation rate (%) of the plates in each comparative example and each embodiment were calculated, and the results are summarized in Table 1 and Table 2.
[0051] Table 1
[0052] Table 2
[0053] According to Tables 1 and 2, on day 0 of aging, the tensile strength of the boards prepared in Examples 1 to 6 was significantly higher than that in Comparative Example 1, indicating that the epoxy crosslinking layer formed by the bisphenol A type epoxy resin solution in the processing aid can significantly enhance the tensile strength of the boards. The impact strength of the boards prepared in Examples 1 to 6 was significantly higher than that in Comparative Examples 2 and 3, indicating that grafting urethane flexible segments onto the epoxy crosslinking layer and constructing an elastic layer mainly composed of PBA can enhance the toughness of the boards. The tensile strength and impact strength of the boards prepared in Examples 1 to 6 were both significantly higher than those in Comparative Example 4, indicating that constructing a BA-MMA copolymer outer layer on the elastic layer helps to uniformly disperse the processing aid and avoid stress concentration caused by agglomeration.
[0054] On the 200th day of aging, the attenuation rate of tensile strength and the attenuation rate of impact strength of the boards prepared in Examples 1 to 6 were significantly lower than those in Comparative Examples 2 and 3. This indicates that grafting urethane flexible segments onto the epoxy crosslinking layer and constructing an elastic layer mainly composed of PBA can effectively prevent moisture from penetrating the processing aids, maintain the structural stability of the processing aids, and improve the long-term stability of the boards in high temperature and high humidity environments.
Claims
1. A preparation process for a processing aid for tensile-resistant CPVC sheets, characterized in that, Includes the following steps: S1. Disperse glass fibers in KH-550 hydrolysate, stir and react. After washing and drying, disperse them in bisphenol A epoxy resin solution, heat and stir and react. After washing and drying, disperse them in ODI solution, heat and stir and react. After washing, disperse them in GMA solution, heat and stir and react. After washing and drying, obtain modified glass fibers. S2. Add dispersant to deionized water and mix well to obtain a dispersion. Disperse the modified glass fiber in the dispersion, add initiator and BA, heat and stir to react. Add initiator and MMA, stir to react, and obtain the processing aid after washing and drying.
2. The preparation process of a processing aid for tensile CPVC sheets according to claim 1, characterized in that, The KH-550 hydrolysate is prepared by mixing anhydrous ethanol, KH-550, and deionized water, adding acetic acid solution to adjust the pH to 4-5, and stirring at 300-400 rpm for 1.5-2.5 h to obtain the KH-550 hydrolysate.
3. The preparation process of a processing aid for tensile CPVC sheets according to claim 1, characterized in that, The bisphenol A type epoxy resin solution is obtained by mixing bisphenol A diglycidyl ether, bisphenol A type epoxy resin with a degree of polymerization of 2, and acetone.
4. The preparation process of a processing aid for tensile CPVC sheets according to claim 1, characterized in that, The ODI solution is obtained by mixing ODI, ethyl acetate, and DBTDL in an inert atmosphere.
5. The preparation process of a processing aid for tensile CPVC sheets according to claim 1, characterized in that, The GMA solution is obtained by mixing GMA, HQ, and THF.
6. The preparation process of a processing aid for tensile CPVC sheets according to claim 1, characterized in that, In step S1, glass fiber is added to KH-550 hydrolysate and stirred at 700-800 rpm for 15-25 min, then at 300-400 rpm for 1-2 h. After washing with anhydrous ethanol and drying, it is added to bisphenol A epoxy resin solution and stirred at 700-800 rpm for 15-25 min. The temperature is raised to 65-70℃ and stirred at 300-400 rpm for 2-3 h. After washing with acetone, it is dried in an environment of 50-60℃ and 8-10 kPa for 2-3 h under an inert atmosphere. Add to ODI solution, stir at 700-800 rpm for 15-25 min, heat to 55-65℃, stir at 300-400 rpm for 1-2 h, wash with ethyl acetate and THF, then add to GMA solution, stir at 700-800 rpm for 15-25 min, heat to 60-70℃, stir at 300-400 rpm for 1.5-2.5 h, wash with THF and ethyl acetate, then dry in an environment of 50-60℃ and 8-10 kPa for 2-3 h to obtain modified glass fiber.
7. The preparation process of a processing aid for tensile CPVC sheets according to claim 6, characterized in that, The drying temperature is 100-110℃, and the drying time is 2-3 hours.
8. The preparation process of a processing aid for tensile CPVC sheets according to claim 1, characterized in that, In step S2, modified glass fiber is added to the dispersion, stirred at 700-800 rpm for 20-30 min, initiator and BA are added and mixed, the temperature is raised to 70-80℃, stirred at 300-400 rpm for 1.5-2.5 h, initiator and MMA are added, stirred at 350-400 rpm for 2-3 h, filtered, washed with deionized water and anhydrous ethanol, and dried in an environment of 60-70℃ and 6-8 kPa for 4-6 h to obtain the processing aid.
9. A processing aid for tensile-resistant CPVC sheets, characterized in that, The tensile-strength CPVC sheet processing aid is prepared by the process described in any one of claims 1-8, comprising the following raw materials in parts by weight: 15-20 parts modified glass fiber, 18-25 parts BA, 0.6-1.0 parts initiator, and 3-5 parts MMA; wherein the modified glass fiber comprises the following raw materials in parts by weight: 17-25 parts glass fiber, 210-215 parts KH-550 hydrolysate, 142-155 parts bisphenol A epoxy resin solution, 115-129 parts ODI solution, and 143-156 parts GMA solution; wherein the modified glass fiber has a length of 1-3 mm and a diameter of 7-13 μm; and wherein the initiator is KPS.
10. The processing aid for tensile CPVC sheets according to claim 9, characterized in that, The KH-550 hydrolysate comprises the following raw materials in parts by weight: 275-286 parts anhydrous ethanol, 28-35 parts KH-550, and 16-20 parts deionized water; the bisphenol A epoxy resin solution comprises 25-35 parts bisphenol A diglycidyl ether, 5-9 parts bisphenol A epoxy resin with a degree of polymerization of 2, and 280-290 parts acetone; the ODI solution comprises 4-8 parts ODI, 95-106 parts ethyl acetate, and 0.2-0.3 parts DBTDL; the GMA solution comprises 10-16 parts GMA, 0.02-0.04 parts HQ, and 205-217 parts THF; the dispersion comprises 3-5 parts dispersant and 240-255 parts deionized water; the dispersant is SDS.
Citation Information
Patent Citations
A heat-resistant and high-temperature resistant PVC power pipe and its preparation method
CN111423673B
Novel durable plastic-wooden composite sheet material
CN102796331A
Chlorinated polyvinyl chloride tube stock and preparation method thereof
CN105255079A
Flame-retardant CPVC tubular product and preparation method thereof
CN108164896A
Heat-resistant high-temperature-resistant PVC electric power pipe and preparation method thereof
CN111423673A
Cited By
Quick-drying moisture curing agent and preparation method thereof
CN122037128A